East Asian International Students and Psychological Well-Being: A Systematic Review - Li, Jiaqi; Wang, Yanlin; Xiao, Feiya (Journal of International Students, 2014)
The present article reports a systematic review of the studies related to psychological well-being among East Asian international students. A total of 18 quantitative studies published in peer-reviewed journals from 2000 to 2011 were reviewed. Our review revealed three major results: (1) a majority of researchers (n=13, 72.2%) tend to choose Chinese international students as a representative of East Asian and Asian international students in their studies; (2) studies on psychological well-being of East Asian international students are closely associated with the following variables: length of stay in host country, English proficiency, attitudes toward seeking help, depression, and acculturation; (3) depression was the most frequently reported variable (n=6,33.3%), followed by acculturation (n=5, 27.8%). Recommendations for further research in psychological well-being were provided.